1996
DOI: 10.1051/jp1:1996171
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of the Bechgaard Salts and Related Compounds

Abstract: Structural aspects of the Bechgaard salts (TMTSF)2X and related 2:1 salts, mostly based on the sulfur donors TMTTF and BCPTTF as well as on the hybrid TMDTDSF donor, are considered in relationship with their physical properties. The basic structure of these salts is reviewed with a special emphasize on the dimerization of the organic stack and on the disorder of the anions (X). Then the density waves instabilities driven by the donor stacks are discussed. It is shown in particular that (TMTSF)2PF6 exhibits a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
291
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(303 citation statements)
references
References 1 publication
12
291
0
Order By: Relevance
“…45 If f -wave is competitive against d-wave even in the absence of strong charge fluctuations, it is likely that f -wave dominates over d-wave in the actual (TMTSF) 2 X, where 2k F CDW actually coexists with SDW. 18,19 For the 2D system, the calculation results (at least for the open shell filling) support presence of attractive interaction in the triplet pairing channel. However, singlet d x 2 −y 2 pairing dominates over all the triplet pairings considered in the present study at the band filling n ≃ 4/3, which corresponds to Sr 2 RuO 4 , in agreement with the FLEX calculation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…45 If f -wave is competitive against d-wave even in the absence of strong charge fluctuations, it is likely that f -wave dominates over d-wave in the actual (TMTSF) 2 X, where 2k F CDW actually coexists with SDW. 18,19 For the 2D system, the calculation results (at least for the open shell filling) support presence of attractive interaction in the triplet pairing channel. However, singlet d x 2 −y 2 pairing dominates over all the triplet pairings considered in the present study at the band filling n ≃ 4/3, which corresponds to Sr 2 RuO 4 , in agreement with the FLEX calculation.…”
Section: Discussionmentioning
confidence: 66%
“…16 A similar proposal has been made by Fuseya et al 17 In fact, the coexistence of 2k F spin and charge density wave has been reported experimentally. 18,19 However, a recent renormalization group study by Fuseya et al 20 has suggested that p-wave pairing dominates over f -wave pairing in quasi-1D systems.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this point, a transport experiment has indicated that the repulsive interaction in θ-(BEDT-TTF) 2 MZn(SCN) 4 (M = Cs,Rb) is long-range [44]. In fact, the presence of such a distant interaction has also been pointed out theoretically [45][46][47]49] for quasi-one-dimensional organic compounds (TMTSF) 2 X in the context of coexisting 2k F spin and 2k F charge density waves [50,51] and spin triplet pairing superconductivity for a review e.g. [48,49], [52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 91%
“…here expressed in units of the reciprocal lattice vector [92,66]. The periodic potential thus created connects two Fermi points along the b direction and opens a gap which doubles the unit cell along that direction.…”
Section: The Symmetry Of the Anionsmentioning
confidence: 99%
“…of the molecular site energy leading in turn to an additional increase of the preexisting charge gap due to on-site correlations and Umklapp scattering [66] (vide-infra). The case of…”
mentioning
confidence: 99%